Taken - Crais, Robert, 1953- (Berkley Books, 2013)
When Nita Morales hires Elvis Cole to find her missing daughter, she's sure it's a ruse orchestrated by the girl and her boyfriend. She's wrong. They've been taken by bajadores- border bandits who prey on the innocent by buying, selling, and disposing of victims like commodities. Cole and Joe Pike start an undercover investigation to find the couple, but their plan derails into a nightmare. Cole disappears, and it is left to Pike to burn through the murderous world of human traffickers to find his friend as well as the missing young people. But he may already be too late. "Crais keeps the reader off-balance with...unexpected plot twists and a breathless pace that makes you feel as if you're smack in the middle of an action film." - The Huffington Post "[Crais's] bestselling Elvis Cole/Joe Pike series gets better with every new book, and...Taken is no exception." - The Oregonian